2013
DOI: 10.2478/s11756-013-0190-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fatty acid composition among selected amaranth grains grown in two consecutive years

Abstract: The oil of amaranth grain (Amaranthus spp.) is a rich source of poly-unsaturated fatty acids. In this study, we tested 10 amaranth samples representing two species (Amaranthus cruentus and Amaranthus hypochondriacus) in two consecutive years (2010, 2011). Grain oils were analysed by gas chromatography for their fatty acids profile. In 2010, oil content ranged from 6.4-8.2% for A. cruentus and 6.3-7.9% for A. hypochondriacus. In 2011, the level was 7.1-8.2% and 6.6-8.7% for A. cruentus and A. hypochondriacus, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 25 publications
16
25
1
Order By: Relevance
“…In the oils of the studied amaranth varieties, omega-3-alpha-linolenic acid was found in the range of 1.17% -1.65 %. Earlier has been established a positive correlation between amaranth seed oil and oleic acid contents (Hlinková et al 2013). Similar results were found in our work since Kharkov and Helios varieties had higher oiliness degree and oleic acid content.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the oils of the studied amaranth varieties, omega-3-alpha-linolenic acid was found in the range of 1.17% -1.65 %. Earlier has been established a positive correlation between amaranth seed oil and oleic acid contents (Hlinková et al 2013). Similar results were found in our work since Kharkov and Helios varieties had higher oiliness degree and oleic acid content.…”
Section: Resultssupporting
confidence: 92%
“…Similar results were found in our work since Kharkov and Helios varieties had higher oiliness degree and oleic acid content. Besides, the negative correlation between oleic acid and linoleic acid quantities corresponds to results in 10 amaranth samples of A. cruentus and A. hypochondriacus (Hlinková et al 2013). Molar ratios of predominant unsaturated oleic (C 18:1) and linoleic (C 18:2) acids correspond to previous results in 5 Amaranthus accessions Table 3.…”
Section: Resultssupporting
confidence: 84%
“…These results are in agreement with other works (Singhal and Kulkarni, 1988;Prakash and Pal, 1992;Prakash et al, 1995;He and Corke, 2003;Hlinková et al, 2013).…”
Section: Oil Content and Fatty Acids Compositionsupporting
confidence: 83%
“…In fact, the seed oil is characterised by high levels of unsaturated fatty acids (UFA) (Hlinková et al, 2013), whose important health benefits in lowering the cholesterol and triacylglycerol concentrations, are very well documented (Kris-Etherton et al, 1999). It has been demonstrated, in fact, that the consumption of polyunsaturated fatty acids (PUFA) decreases the ratio of total cholesterol to high-density lipoprotein cholesterol, improves insulin resistance (Mensink et al, 2003) and reduces systemic inflammation (Summers et al, 2002;Ferrucci et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The oil content of amaranth grain ranged from 58 to 71 g/kg for Amaranthus cruentus (Berganza et al, 2003), while Hlinková et al (2013) showed that oil content of Amaranthus cruentus ranged from 64 to 82 g/kg and from 63 to 87 g/kg for Amaranthus hypochondriacus.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%